The specificity, situational modulations, and behavioral correlates of parent-child neural synchrony - Liu, Yi; Li, Jiaxin; Wang, Qi; Li, Yarong (Frontiers in Human Neuroscience, 2022)
In recent years, aiming to uncover the neural mechanism of parent-child interaction and link it to the children’s social development, a newly developed index, namely, parent-child inter-brain neural synchronization (INS) has attracted growing interest. Existing studies have mainly focused on three aspects of the INS; these are the specificity of the INS (i.e., stronger INS for parent-child dyads than stranger-child dyads), the situational modulations of the INS (i.e., how the valence of the situation or the types of interaction modulate INS), and the associations between the INS and the state-like behavioral tendencies or trait-like individual features of the parents and children. This review summarizes the existing findings in line with these three topics and provides preliminary suggestions to promote parent-child INS. In the meanwhile, the inconsistent findings and unstudied questions were discussed, opening new avenues for future studies.